Targeting hunger or votes? The political economy of humanitarian transfers in Malawi - Duchoslav, Jan; Kenamu, Edwin; Thunde, Jack (International Food Policy Research Institute, 2022)
Do electoral considerations play a role in the targeting of humanitarian transfers? We analyze the targeting of direct cash and food transfers distributed in Malawi in response to an exceptionally poor harvest following a late and erratic rainy season of 2015-16. Combining household survey data on transfers with a remotely sensed measure of drought and with the results of the 2014 and 2019 parliamentary elections, we show that transfers were disproportionately targeted at marginal constituencies. Rather than distributing the transfers based solely on need or mobilizing its tribal base, the government attempted to persuade swing voters to support its candidates in the next elections. We found no evidence that this strategy was successful at increasing the vote of ruling party candidates in subsequent elections.